The Impact of Digital Investments on Firm's Competitiveness - Sanel Volarić (6th International OFEL Conference on Governance, Management and Entrepreneurship. New Business Models and Institutional Entrepreneurs: Leading Disruptive Change. April 13th - 14th, 2018, Dubrovnik, Croatia, 2018)
The initial significant technological investments in business automation during 60-ies and 70-ties were very soon followed by focus of both scholars and business community in defining models that depict the influence of information and communication technological (ICT) investments on different aspects of firm's performance. The foundations of the scholar approach in the area were set up by Porter (1985.) when he challenged established and unquestioned positive influence of ICT investments on firm's competitiveness. He stressed that such investments are not necessarily “strategically beneficial” and may erode competitiveness of firms and industries. As well, a decade before dawn of digital revolution, alignment of ICT/digital strategy with overall strategic plans was proved to be the main driver of positive influence of ICT investments on firm's performance and competitiveness. The fact was iteratively proved in many later papers while need of “alignment” gradually evolved in “integration” of digital strategy in firm's comprehensive digital business strategy. Variety of models and nomological networks have been developed to define and depict the influence of investments in digital resources (IT infrastructure, HR resources, alignment with business strategy, etc.) on firm's key performance indicators. For example, Sambamurthy et al. (2003.) argue that information technology investments and capabilities influence firm performance through three significant organizational capabilities (agility, digital options, and entrepreneurial alertness) and strategic processes (capability-building, entrepreneurial action, and co-evolutionary adaptation). Mithas et al. (2011.) developed a conceptual model linking IT-enabled information management capability and firm's performance mediated by three organizational capabilities (customer, process and performance management capabilities). These and other papers emphasize the strategic role of ICT competences that are an antecedent of successful competitive actions and financial prosperity in moderate to fast-paced business environments. The influence is mediated by developing different dimensions of agility (customer, partnering and operational agility) and competitive actions characteristics (#of competitive actions, complexity of the action repertoire). In digital era established companies will be continuously exposed to digital disruptions initiated by both start-up companies and incumbents that have already successfully passed through digital transformation process.This turbulent competitive landscape, characterized by hyper-competition, increased time-to-market pressures, regulatory changes and rapidly evolving customer demands, can mean both - either an opportunity or a threat depending on firm's capabilities to adopt the new paradigm and develop digitally enabled enterprise agility – ability to persistently detect and seize market opportunities with speed and surprise. The prerequisite for this is an efficient implementation of comprehensive digital business strategy: digital strategy fully integrated in firm's strategic plan.
Keywords: 650; Information-communication technologies (ICT); Digital era; Digital disruption; Digital transformation; Innovativeness; Corporate entrepreneurship; Strategic management; Competitiveness; Firm's performance